Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Pemahaman Siswa Dalam Pembelajaran PAI - Maria, Anly; Amani, Adinda Rania Khairunnisa (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Student comprehension is the ability to understand instructions or problems, interpret them, and rephrase them in one's own words. Currently, comprehension levels among students in Islamic Religious Education (PAI) are still low, as evidenced by students' inability to properly understand and explain the material presented, or to summarize it using their own words. Therefore, innovative and varied learning models are needed, such as the cooperative learning model "Make a Match," which can be applied across different classes and subjects. The cooperative learning model "Make a Match" involves students finding pairs while learning about a concept or topic in an enjoyable environment, thereby enhancing their comprehension. This research aims to describe the impact of the cooperative learning model "Make a Match" on student comprehension in PAI. The research method employed is experimental. Data collection techniques include observation, written tests, and documentation studies. Data processing was conducted through statistical data analysis. The population of this study consists of all eighth-grade students at SMPN 1 Tarogong Kidul Garut, totaling 370 students. The sample includes 33 students from class VIII A as the experimental group and 33 students from class VIII J as the control group. The results show that the average pre-test score for the experimental class was 71.15, while the control class scored 71.52. After implementing the "Make a Match" cooperative learning model, the average post-test score in the experimental class increased to 89.06, compared to 82.24 in the control class, which used the lecture method. Based on the t-test results, the calculated t-value (5.26) was greater than the critical t-value (2.00). Thus, it can be concluded that the "Make a Match" cooperative learning model has a significant impact on improving student comprehension in PAI classes at SMPN 1 Tarogong Kidul Garut.  Keywords: Cooperative Learning Model "Make a Match"; Student Comprehension; Islamic Religious Education